Jorge Luis Borges’s Partial Argentine Ulysses: A Foundational (Mis-)Translation - Waisman, Sergio (TTR)

(untitled) (Association canadienne de traductologie, 2006)
AbstractIn this article, I first introduce the deconstructionist idea of the error (drawn primarily from Paul de Man) as a potentially productive category, then combine this idea with what I call Borges’s theory of mis-translation, to analyze the foundational role of (mis-)translation in Argentine literature, focusing specifically on Borges’s 1925 version of the last page of James Joyce’s Ulysses. I go on to discuss Borges’s theory of mis-translation and its importance within an Argentine as well as a transnational context. In essays such as “Las versiones homéricas” [The Homeric Versions] and “Los traductores de Las 1001 Noches” [The Translators of The 1001 Nights], Borges posits that translations are not necessarily inferior to originals, and that a translation’s merits may actually reside in its creative infidelities. After delineating Borges’s irreverent position on translation, I carefully analyze Borges’s 1925 translation of the last page of Joyce’s Ulysses, to examine how Borges uses (mis-)translation to create a partial Argentine version of Joyce’s Modernist novel, which serves, among other things, a paradoxical foundational role in Argentine and Latin American literatures.